Two Humanist Views on the Art of History: Filippo Beroaldo the Elder and Giorgio Valla. - Pineda, Victoria; Villalba, Joaquín (International Journal of the Classical Tradition, 2021)
The article presents the discussion on the list of publications dealing with humanist historiographical theory including early humanists producing a series of letters, prefaces, orations, invectives, and short extracts.